Basin margin sediment wedge build out of the Eastern Niger Delta: application of shelf-edge trajectory pattern studies - Okwudiri A. Anyiam; Nicholas Hoggmascall; Daniel K. Amogu (Journal of Petroleum Exploration and Production Technology)
Abstract The understanding of how basin margin sediment wedge builds out causes shelf-edge migration with time is approached based on shelf-edge trajectory pattern analysis using a high-resolution mega-merge seismic data from the eastern Niger Delta, Nigeria. The study focuses on a seismic dip transect traversing the Greater Ughelli, Central Swamp, Coastal Swamp and the Shallow Offshore Depobelts of the Niger Delta. On the regional dip transects, shelf-edge sediments occur as clinoform-bearing wedges at and immediately updip of the shelf-slope break. The shelf edge is deeply buried (> 2–4 s, twt), around the Greater Ughelli and Central Swamps. But with changing structural style, sudden change of ascending shelf edge around the Central Swamp was observed. The huge listric growth fault in the Coastal Swamp; around Bonny area, once again cut the shelf edge into half, rotated it along the listric fault and buried it distally. Several depositional packages show low to moderate ascending shelf-edge trajectory with progradational to aggradational clinoform growth that is characterized by thin sand sheets across most of the shelf and upper slope, though few are also characterized by progradational clinoform growth with thick sand on the shelf, upper-tolower slope and basin floor. The deposition is usually on the Outer Shelf Terrace (OST) which is regressive in a flat and rising trajectory style. This study has demonstrated that accommodation and sediment flux are the dominant controls on how the study basin’s sediment wedge built out, whereby limited accommodation promotes sediments with significant shelf-edge advance and descending trajectories, while increasing accommodation promotes ascending trajectories and increased deposition on the outer shelf. The greater sediments on the Outer Shelf Terrace and the shelf margin than on the slope gives more hydrocarbon prospectivity search around the outer shelf and shelf margin.